2014
DOI: 10.1007/s10822-014-9779-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insight into γ–γ tubulin lateral interactions within the γ-tubulin ring complex (γ-TuRC)

Abstract: γ-Tubulin is essential for the nucleation and organization of mitotic microtubules in dividing cells. It is localized at the microtubule organizing centers and mitotic spindle fibres. The most well accepted hypothesis for the initiation of microtubule polymerization is that α/β-tubulin dimers add onto a γ-tubulin ring complex (γTuRC), in which adjacent γ-tubulin subunits bind to the underlying non-tubulin components of the γTuRC. This template thus determines the resulting microtubule lattice. In this study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…In contrast, the decomposition of binding free energy calculated on the basis of MM‐PBSA into per residue basis was not so far possble because PB nonpolar solvation energies are currently not decomposable using Amber simulation package. Similar studies have been reported earlier in the insulin dimer, TCR‐p‐MHC, Ras‐Raf, and Ras‐RalGDS complexes and γ‐γ tubulin dimers . The results from these studies demonstrated good correlations between the calculated per residue binding free energy and the experimental binding free energies differences for the alanine mutants.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, the decomposition of binding free energy calculated on the basis of MM‐PBSA into per residue basis was not so far possble because PB nonpolar solvation energies are currently not decomposable using Amber simulation package. Similar studies have been reported earlier in the insulin dimer, TCR‐p‐MHC, Ras‐Raf, and Ras‐RalGDS complexes and γ‐γ tubulin dimers . The results from these studies demonstrated good correlations between the calculated per residue binding free energy and the experimental binding free energies differences for the alanine mutants.…”
Section: Resultssupporting
confidence: 87%
“…Similar studies have been reported earlier in the insulin dimer, 53 TCR-p-MHC, 54 Ras-Raf, and Ras-RalGDS 55 complexes and g-g tubulin dimers. 56 The results from these studies demonstrated good correlations between the calculated per residue binding free energy and the experimental binding free energies differences for the alanine mutants. Toward this end the predictive binding energy (DG bind,GB ) between GCP4 and g-tubulin was decomposed into contributions from the residues of the two partners.…”
Section: Per Residue Energy Contribution To the Binding Free Energymentioning
confidence: 69%
“…After understanding the dynamic properties of P5091 at all different sites, we calculatedthe free energy of binding ( Δ G bind ) [ 32 34 ]. The results indicate that P5091 binds more favorably at S7 ( Δ G bind = −34.23 kcal/mol) than S4 ( Δ G bind = −19.84 kcal/mol) ( Supplementary Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Positive values of △△G bind indicate the corresponding residue provides the favorable contribution, while negative values suggest the related residue produces unfavorable contribution …”
Section: Methodsmentioning
confidence: 99%